Implementation and evaluation of Parkinson disease management in an outpatient clinical pharmacist–run neurology telephone clinic - Stefan, Teodora Cristina (Ment Health Clin, 2018)
Parkinson disease (PD) is a progressive, debilitating neurodegenerative disease that often requires complex pharmacologic treatment regimens. Prior to this clinic, there was no involvement of a clinical pharmacy specialist (CPS) in the outpatient neurology clinic at the West Palm Beach Veterans Affairs Medical Center. This was a prospective, quality-improvement project to develop a clinical pharmacist–run neurology telephone clinic and evaluate pharmacologic and nonpharmacologic interventions in an effort to improve the quality of care for patients with PD. Additionally, the CPS conducted medication education groups to 24 patients with PD and their caregivers, if applicable, at this medical center with the purpose of promoting patient knowledge and medication awareness. Medication management was performed via telephone rather than face to face. Only patients with a concomitant mental health diagnosis for which they were receiving at least one psychotropic medication were included for individual visits due to the established scope of practice of the CPS being limited to mental health and primary care medications. Data collection included patient and clinic demographics as well as pharmacologic and nonpharmacologic interventions made for patients enrolled from January 6, 2017, through March 31, 2017. A total of 49 pharmacologic and nonpharmacologic interventions were made for 10 patients. We successfully implemented and evaluated a clinical pharmacist–run neurology telephone clinic for patients with PD. Expansion of this clinic to patients with various neurological disorders may improve access to care using an innovative method of medication management expertise by a CPS.